Developing reading skills : beginning - Markstein, Linda; Hirasawa, Louise (Rowley, Mass. : Newbury House, 1981)
A textbook designed to strengthen reading skills by exposing readers to material which promotes vocabulary development, structural analysis, and relational and inferential analysis.
Includes bibliographical references.
Keywords: English language -- Textbooks for foreign speakers; Readers